Effect of ball mill method on microstructure and electrical properties of BaTiO3 based PTCR ceramics. (July 2015) - Ma, Mingsheng; Wang, Yilin; Lu, Yiqing; Wu, Wenjun; Li, Yongxiang
Abstract: This work focuses on the temperature stability of resistance below the switching temperature of positive temperature coefficient resistor (PTCR) ceramics. The BaTiO3 based PTCR powders were grinded by conventional ball milling and high-energy ball milling. Particle size distribution analysis showed that high-energy ball milling was much more efficient for particle size reduction. It was found that the PTCR ceramic with 3000 rpm for 1 h high-energy ball milling has uniform grain size distribution. The measurement results of the resistance–temperature characteristics of PTCR ceramics indicated that the temperature stability of resistance below the switching temperature of PTCR ceramics could be improved by high-energy ball milling, and the optimum temperature stability of resistance below the switching temperature existed in the sample of 3000 rpm-1 h. The capacitance–temperature characteristics of PTCR ceramics were also investigated.